2019
DOI: 10.1002/alr.22277
|View full text |Cite
|
Sign up to set email alerts
|

Formation of papillary mucosa folds and enhancement of epithelial barrier in odontogenic sinusitis

Abstract: Background: Odontogenic sinusitis (OS) presents more satisfactory therapeutic effect a er endoscopic surgery compared with chronic rhinosinusitis (CRS) of other origin. The aim of the present study was to investigate the clinical characteristics, morphological features, and epithelial barrier function of sinus mucosa of OS and discuss the possible relationship with good prognosis. Methods:A total of 25 subjects with OS, 7 CRS without nasal polyps (CRSsNP), 10 CRS with nasal polyps (CR-SwNP), and 9 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(27 reference statements)
0
14
2
Order By: Relevance
“…We assume that PM2.5 might have impact on both mRNA and protein levels. ZO-1 and claudin-7 mRNA elevation in response to PM2.5 exposure might reflect a defensive feedback mechanism of normal epithelial barrier, which has been observed in epithelium exposed to anaerobic bacteria or Staphylococcus aureus 3233. On the other hand, PM2.5 might also affect TJ molecules expression post-transcriptionally by different mechanisms, which called for further studies.…”
Section: Discussionmentioning
confidence: 95%
“…We assume that PM2.5 might have impact on both mRNA and protein levels. ZO-1 and claudin-7 mRNA elevation in response to PM2.5 exposure might reflect a defensive feedback mechanism of normal epithelial barrier, which has been observed in epithelium exposed to anaerobic bacteria or Staphylococcus aureus 3233. On the other hand, PM2.5 might also affect TJ molecules expression post-transcriptionally by different mechanisms, which called for further studies.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, histopathological investigation of intractable OMS revealed that the maxillary sinus mucosa appeared gyrus‐like in appearance and that the number of ciliated epithelial cells did not decrease, goblet cells were not hypertrophic and the secretions were not viscous but purulent. Zhang et al reported that small papillary protrusions could be seen in the maxillary sinus mucosa of OMS under nasal endoscopy, similar to the morphological behavior, which also presented as papillary folds in the surface of the epithelium . And papillary‐like fold mucosa of OMS was covered with intact pseudostratified columnar ciliated epithelium .…”
Section: Discussionmentioning
confidence: 84%
“…Zhang et al reported that small papillary protrusions could be seen in the maxillary sinus mucosa of OMS under nasal endoscopy, similar to the morphological behavior, which also presented as papillary folds in the surface of the epithelium . And papillary‐like fold mucosa of OMS was covered with intact pseudostratified columnar ciliated epithelium . Raman et al reported that odontogenic chronic rhinosinusitis exhibited increased moderate‐severe inflammation compared to chronic rhinosinusitis without nasal polyp, had decreased squamous metaplasia and fibrosis compared to chronic rhinosinusitis with nasal polyp, and exhibited some eosinophilia but to a lesser extent than chronic rhinosinusitis with nasal polyp .…”
Section: Discussionmentioning
confidence: 88%
“…Our previous histopathological investigation of intractable OMS revealed that the maxillary sinus mucosa appeared gyrus-like in appearance and that the number of ciliated epithelial cells did not decrease, goblet cells were not hypertrophic and the secretions were not viscous but purulent [14] . Zhang et al reported similar histopathological findings that the maxillary sinus mucosa of OMS presented as papillary folds in the surface of the epithelium and papillary-like folded mucosa was covered with intact pseudostratified columnar ciliated epithelium [15] .…”
Section: Histopathology Of the Maxillary Sinus Mucosa Of Omsmentioning
confidence: 75%